2021
DOI: 10.1002/jclp.23108
|View full text |Cite
|
Sign up to set email alerts
|

Future orientation in successful therapies: Expanding the concept of goal in the working alliance

Abstract: Objective: To better understand how therapists facilitate client goal attainment in therapy, we analyzed therapists' future-oriented actions in good outcome cases in which clients recorded high ratings on goal items in the Working Alliance Inventory-Short Revised. Method: We selected clients who were within the clinical range (OQ-45.2) at pretreatment, demonstrated reliable change at the end of treatment, and recorded high WAI client goals scores early in treatment. Qualitative analyses of transcripts of the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 91 publications
0
7
0
Order By: Relevance
“…However, it rarely happens this way. It seems that experienced therapists in highalliance and successful cases rarely explicitly discuss the very specific goals of treatment, al though they do induce a future orientation through various tech niques 6,7 . This raises the question of what is meant by goals of treatment, particularly the level of specificity of such goals.…”
Section: Historical Roots and Definition Of The Alliance Conceptmentioning
confidence: 99%
“…However, it rarely happens this way. It seems that experienced therapists in highalliance and successful cases rarely explicitly discuss the very specific goals of treatment, al though they do induce a future orientation through various tech niques 6,7 . This raises the question of what is meant by goals of treatment, particularly the level of specificity of such goals.…”
Section: Historical Roots and Definition Of The Alliance Conceptmentioning
confidence: 99%
“…Adjusting intensity by, for instance, letting children set the treatment agendas or accepting that children might need to avoid eye contact is consistent with earlier studies on children’s needs and experiences in therapy (e.g., McCrea et al, 2016; Lindqvist et al, 2022). Linguistic devices, such as hedging (mitigating language, e.g., Tables 4 and 5), are also documented as part of goal-related processes in successful therapies (Oddli et al, 2021). In emotionally loaded situations, the soothing function of mitigating language can also protect practitioners and enable them to reconcile complex situations (Ruch et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In-depth interview analyses have demonstrated how therapists draw on their extended repertoire of knowledge sources, involving embodied, implicit decision making and clinical intuition (Bernhardt et al, 2021;Oddli & Halvorsen, 2014;Oddli & McLeod, 2017;Råbu et al, 2021). Qualitative analyses of therapy sessions have identified how decisions evolve as therapists make use of micro-cues along with distinctive linguistic manners, to involve the patient in a meaningful interaction about relevant tasks in therapy and future goals and directions (Oddli & McLeod, 2017;Oddli et al, 2021;Oddli & Rønnestad, 2012;von der Lippe et al, 2019). These studies serve to elaborate on how therapists contribute to the working alliance and other factors associated with effective therapies, such as motivation, goals, shared decision making, and responsiveness.…”
Section: The Responsive Therapist and Contextual Designs: Findings Fr...mentioning
confidence: 99%
“…One example is a line of qualitative studies of "master therapists" or "supershrinks" who are identified according to their reputation within a community of practice; that is, studies of the reputedly excellent therapists (e.g., Hansen et al, 2015;Jennings & Skovholt, 1999;Skovholt & Jennings, 2016;Skovholt & Rønnestad, 1992, 1995. Examples are qualitative analyses of good-outcome and high-alliance processes with reputable, experienced therapists (e.g., Oddli et al, 2021), comparative qualitative analyses of the processes of good-and poor-outcome cases (e.g., Hansen et al, 2015;von der Lippe et al, 2019), and therapists' strategies when facing difficult impasses (Moltu & Binder, 2011).…”
Section: Master Therapists Supershrinks and Comparative Studies Of Po...mentioning
confidence: 99%